A hospital-based prospective study of sickle cell disease in children of Eastern India - Bighneswar Senapati; Bharati Das; Sarbeswar Pradhan; Arakhita Swain; Aryan Jaiswal; Nirmal Kumar Mohakud (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Background: Sickle cell disease (SCD), sickle cell anemia (SCA), and sickle beta-thalassemia (SBT) are due to a mutated gene of hemoglobin (Hb), which makes the red blood cells sickle-shaped and decreases their oxygen-carrying capacity. The disease is prevalent in the rural population of Odisha. Clinical presentation of SCA and SBT is similar, though there is a difference in treatment modality for both the entities. However, there are a few studies to delineate between these two diseases in children below 15 years. Aim: A hospital-based prospective study was conducted in eastern India to assess the clinicohematological profile of children with SSA and SBT. Methods: The prospective study was conducted in Srirama Chandra Bhanja Medical College, Cuttack, Odisha, from January to December 2020. A total of 43 confirmed cases by Hb electrophoresis of SCD were enrolled. Detailed clinical manifestations and hematological and biochemical tests were recorded as per the pro forma. Results: Clinical findings validated the major manifestations of SCD as splenomegaly, hepatomegaly, jaundice, fever, abdominal pain, crisis, and myopathy. Most of the SCD patients have severe anemia (range; 2.7–12.4 g/dL) at presentation. Splenomegaly was found in 43.8% of SCA versus 85.2% of SBT cases. Jaundice was more marked in SCA (62.5%) compared to SBT (48.1%) cases. Both the mean corpuscular Hb and mean corpuscular volume are more in SCA compared to SBT. Conclusions: Presentation of SCA is more severe compared to SBT. Enhanced implementation of newborn screening programs in Odisha state will help in reduction of the disease burden and morbidity due to SCD.